The Relationship of Body Mass Index with Length of Stay in Acute Appendicitis Patients Who Have Undergoing Open Appendectomy at RSUS Lippo Village Karawaci Hospital - Christianto, Putra Niko Laksamana Oceano; Sudirman, Taufik (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background : Appendicitis is an inflammation that occurs in the veriform appendix. The Indonesian Ministry of Health announced that the number of inpatients with appendicitis is the fourth most common disease in Indonesia. Open appendectomy is a procedure for treating appendicitis. Patients who have an open appendectomy procedure require hospitalization for the wound to heal. Various studies have been conducted to find a relationship between body mass index and length of stay in patients with appendicitis but have different results, besides that research on this topic is still minimal in Indonesia. Therefore, this study was conducted to analyze the relationship between body mass index and length of stay in acute appendicitis patients who had undergone open appendectomy. Methods : This study used a cross-sectional study design with a sample population of acute appendicitis patients at Lippo Village Hospital Karawaci. 182 samples were selected using a purposive sampling technique. The research sample data was taken from the patient's medical records and will be tested for analysis using SPSS 25 with the Kruskal Wallis ANOVA method. Result : From 182 research samples, it was found that the median length of stay of patients with different body mass indexes was 3 days. Based on the Kruskal Wallis ANOVA test, there was no significant elationship between gender and length of stay (p > 0.05). Conclusions : This study shows that there is no relationship between body mass index and length of stay in acute appendicitis patients who have undergone open appendectomy.